Purge the evil from among you: Deuteronomy’s social vision of Israel’s social boundaries - Cox, Michael (Zeitschrift für altorientalische und biblische Rechtsgeschichte, 2024)
Cover -- Front Matter -- Contents -- Acknowledgments -- Chapter 1 Introduction -- 1.1 Deuteronomy's Purge Texts: A Brief Introduction -- 1.2 Survey of Secondary Literature -- 1.2.1 Historical Critical Examinations -- 1.2.2 Decalogue and Purge -- 1.2.3 Removal Texts and the Reception of Deuteronomy's Purge Texts -- 1.2.4 The Need for the Current Study -- 1.3 Thesis and Procedure -- Chapter 2 The Social Vision of Deuteronomy -- 2.1 Form, Structure, and Purpose -- 2.1.1 Gerhard von Rad, "Sermon," and One God -- 2.1.2 Deuteronomy's Form: Covenant Document -- 2.1.3 Law Code, Constitution, and Teaching -- 2.1.4 Structure: Superscripts and Discourse Analysis -- 2.1.5 Conclusion -- 2.2 Social Vision and Method of Approach -- 2.2.1 Social Vision and Case-Law: Deuteronomy 12-26 -- 2.2.2 Deuteronomy's Case-Law as If-Plots -- 2.3 Method: Approaching Deuteronomy's Case-Laws as Narrative -- 2.3.1 Level 1: Discourse Frames -- 2.3.2 Level 2: "Case Semantics" and Narrative Frames -- Chapter 3 Deuteronomy's Social Setting -- 3.1 "Segmentary" Society -- 3.1.1 "Nation" -- 3.1.2 "Tribe" -- 3.1.3 "Clan" -- 3.1.4 "Household" -- 3.2 Metaphor and Covenant -- 3.3 Conclusion: Social Responsibility as the Social Context for Removal -- Chapter 4 Boundaries, Deviance, and Persistence -- 4.1 A Schematic Survey -- 4.2 Fredrick Barth and Social Boundary -- 4.3 Boundaries, Deviance, and Persistence in Cognitive Idiom -- 4.3.1 Boundaries -- 4.3.2 Judgment and Deviant Behavior -- 4.3.3 Persistence -- 4.4 Conclusion -- Chapter 5 Phase 1 Conclusion -- Chapter 6 The Language of the Social Boundaries: A Cognitive Semantic Analysis of Deuteronomy's Purge Formula -- 6.1 Basic Concepts of Cognitive Grammar -- 6.2 Relational Profile of = הָרעָ מקִּרִבְּ ֶ -- 6.2.1 A Semantic Survey of מ ן+ קרב + ך -- 6.2.1.1 A Semantic Profile of קֶרבֶ within Deuteronomy.